229k views
4 votes
Pleaseee help I keep getting undefined ​

Pleaseee help I keep getting undefined ​-example-1
User Asmb
by
4.7k points

2 Answers

3 votes

Answer:

4 (Answer B)

Explanation:

Note that we can rewrite the given expression as

{ ∛(-8)}² In words: the square of the cube root of -8

This simplifies to (-2)² which in turn is 4 (Answer B)

User Killnine
by
5.1k points
7 votes

Answer:

Second option "B. 4" is the correct choice.

Explanation:


(-8)^{(2)/(3)}\\\\\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^{(m)/(n)}=\left(-1\right)^{(m)/(n)}\left(a\right)^{(m)/(n)}\\\\=\left(-1\right)^{(2)/(3)}\cdot \:8^{(2)/(3)}\\\\=1\cdot \:8^{(2)/(3)}\\\\=8^{(2)/(3)}\\\\=\left(2^3\right)^{(2)/(3)}=2^{3\cdot (2)/(3)}=2^2\\\\=4

Best Regards!

User Arshaw
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.